2002
DOI: 10.1109/tasc.2002.1018590
|View full text |Cite
|
Sign up to set email alerts
|

Nb/sub 3/Al superconductors

Abstract: Recent progress of Nb 3 Al superconductors is described. A large-current conductor of 46 kA at 13 T, produced from a jelly-roll (JR) Nb/Al composite by a direct diffusion-process, is about to be tested as an insert-coil conductor for fusion magnets. The 1 GHz NMR magnet has given a motivation to do an entirely new approach to Nb 3 Al processing that allows a dramatic improvement in high-field characteristic. The RHQT process produces a stoichiometric Nb 3 Al with fine-grain structures via a bcc supersaturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…It has been reported that when a RHQ treatment is applied to Nb and Al raw materials, a solid solution of NbAl y with a bcc structure is formed [6][7][8][9][10][11][12]. Upon further heat treatment, this undergoes an A15 phase transformation to form Nb 3 Al.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that when a RHQ treatment is applied to Nb and Al raw materials, a solid solution of NbAl y with a bcc structure is formed [6][7][8][9][10][11][12]. Upon further heat treatment, this undergoes an A15 phase transformation to form Nb 3 Al.…”
Section: Introductionmentioning
confidence: 99%
“…The sample temperature accuracy is better than ±2 °C. The ramp rate was either 120 °C/h or 800 °C/h (for comparison, the ramp rate during a transformation HT is typically between 200 and 800 °C/h [4]). Unlike in a standard transformation HT, during the 120 °C/h HT the 800 °C plateau has been omitted, and the maximum temperature was 1100 °C, slightly above the Cu melting temperature of 1085 °C.…”
Section: The In Situ Heat Treatment (Ht)mentioning
confidence: 99%
“…The Rapid Heating and Quenching (RHQ) stages are followed by a transformation heat treatment (HT) at relatively low temperature of typically 800 °C, during which the fine grained A15 phase with high Al content is formed from the Nb(Al) SS solid solution [4].…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed applicability of Nb 3 Sn and Nb 3 Al for a superconducting wire of the IL-CS. It was found that since the critical current density J c of a Nb 3 Sn wire in the high magnetic field environment is smaller than that of a Nb 3 Al wire [8], the operation current density J op normalized to J c of the Nb 3 Sn wire is higher than that of the Nb 3 Al wire and above the design limit of J op /J c for the ITER superconducting magnet design. Accordingly, the IL-CS made of Nb 3 Sn has to be thicker than of Nb 3 Al to decrease J op /J c .…”
Section: Inter-linked Central Solenoid Configurationmentioning
confidence: 99%